Kemitraan Sektor Swasta Dalam Layanan Pemadam Kebakaran di Kota Pontianak - Taufiqurrahman, Taufiqurrahman; Wijaya, Holi Bina (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2013)
The fire services is one of public services that should be provided by Pontianak City Government, as one of the cities with high-risk of fire disaster. In order to provide it, Pontianak City Government assisted by private fire-fighters institutions. One of this institutions is BPA Siantan. In conducting its duties, BPA Siantan cooperate with various parties. Then, "How is the partnership relation among BPA Siantan with others to make fire management services?". This research aims to assess BPA Siantan partnership with others to provide fire management services in Pontianak. This research used a qualitative method with case study strategy to get and can describe the research objects deeply and detail. The results indicated that (1) The fire services of BPA Siantan are not appropriate with the Government standards. (2) BPA Siantan cooperate with other parties, such as local community, Communications Forum, City Government, academics, and APKS (Association of Private Fire-Fighters Institutions) in fire management activities. (3), The partnership of BPA Siantan with the others just limited in providing of information and resources. In the future, to improve the fire management services, the partnership pattern of BPA Siantan with other parties can be developed in activity based costing.